2004
DOI: 10.1175/bams-85-9-1355
|View full text |Cite
|
Sign up to set email alerts
|

The RED Experiment: An Assessment of Boundary Layer Effects in a Trade Winds Regime on Microwave and Infrared Propagation over the Sea

Abstract: The Rough Evaporation Duct experiment aimed to see if the effects of ocean waves account for errors in modeling the ranges at which radar and infrared can detect low-flying targets. When radars first came into operation during the late 1930s, they were not expected to detect targets much beyond the geometrical horizon. These early radars, operating at a wavelength of 13 m, generally met expectations. As new radars were rapidly developed, operating at shorter and shorter wavelengths for better target detection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…A general agreement between the measured and predicted field strength and a variety of atmospheric conditions [31]; some discrepancies are reported concerning the fading: the computed fading was not always as deep as the measured one [32]. Another experiment, the Rough Evaporation Duct (RED) experiment [92,93], specifically organized to investigate the effects of ocean waves on the meteorological parameters and, hence, on the evaporation duct, has provided also data for the validation of meteorological and propagation models designed for the marine surface layer. Measurements of microwave propagation loss under evaporation duct conditions were compared to prediction estimates based on the PE given by (1).…”
Section: Validation Of the Pe And Limitations Of 2d Pementioning
confidence: 94%
See 2 more Smart Citations
“…A general agreement between the measured and predicted field strength and a variety of atmospheric conditions [31]; some discrepancies are reported concerning the fading: the computed fading was not always as deep as the measured one [32]. Another experiment, the Rough Evaporation Duct (RED) experiment [92,93], specifically organized to investigate the effects of ocean waves on the meteorological parameters and, hence, on the evaporation duct, has provided also data for the validation of meteorological and propagation models designed for the marine surface layer. Measurements of microwave propagation loss under evaporation duct conditions were compared to prediction estimates based on the PE given by (1).…”
Section: Validation Of the Pe And Limitations Of 2d Pementioning
confidence: 94%
“…The adequacy of the PE method in modeling the radio wave propagation has been also extensively validated by means of comparisons to measured data [27,31,32,[89][90][91][92][93]. Both verification and validation refer to different inhomogeneous environments and a broad range of frequencies and propagation scenarios.…”
Section: Validation Of the Pe And Limitations Of 2d Pementioning
confidence: 99%
See 1 more Smart Citation
“…From our RED measurements we found that, depending upon conditions, the degradation in EO signal could be on the order of tens of percent at a wavelength of 4 µm (Anderson et al, submitted [7], Clarke et al, [8]). …”
Section: Security Classification Of: 17 Limitation Of Abstractmentioning
confidence: 94%
“…SEAS [2][3][4][5] highlighted new approaches for calibration of lidars and to derive aerosol extinction values. RED aerosol data [7,8] allowed estimate the effect of coastal aerosol from breaking waves on visible and IR EO propagation.…”
Section: Impact/applicationmentioning
confidence: 99%